Helping the self help others: self-affirmation increases self-compassion and pro-social behaviors - Lindsay, Emily K.; Creswell, J. David (Frontiers in Psychology, 2014)
Reflecting on an important personal value in a self-affirmation activity has been shown to improve psychological functioning in a broad range of studies, but the underlying mechanisms for these self-affirmation effects are unknown. Here we provide an initial test of a novel self-compassion account of self-affirmation in two experimental studies. Study 1 shows that an experimental manipulation of self-affirmation (3-min of writing about an important personal value vs. writing about an unimportant value) increases feelings of self-compassion, and these feelings in turn mobilize more pro-social behaviors to a laboratory shelf-collapse incident. Study 2 tests and extends these effects by evaluating whether self-affirmation increases feelings of compassion toward the self (consistent with the self-compassion account) or increases feelings of compassion toward others (an alternative other-directed compassion account), using a validated storytelling behavioral task. Consistent with a self-compassion account, Study 2 demonstrates the predicted self-affirmation by video condition interaction, indicating that self-affirmation participants had greater feelings of self-compassion in response to watching their own storytelling performance (self-compassion) compared to watching a peer’s storytelling performance (other-directed compassion). Further, pre-existing levels of trait self-compassion moderated this effect, such that self-affirmation increased self-compassionate responses the most in participants low in trait self-compassion. This work suggests that self-compassion may be a promising mechanism for self-affirmation effects, and that self-compassionate feelings can mobilize pro-social behaviors.